How Sharia Rural Banks and Islamic Fintechs Are Partnering for Financial Inclusion: Indonesian Lessons from the Ground - Abrista Devi; Muhammad Faishal Hidayat; Ghefira Shindy Nofianti (Faculty of Islamic Business and Management, 2025)
This study aims to analyze potential collaboration models between sharia fintech and Bank Pembiayaan Rakyat Syariah (BPRS) in Indonesia and to determine which model offers the highest strategic impact according to expert judgment. Using the Analytic Network Process (ANP), this research evaluates four alternative collaboration models identified through literature review and expert interviews. The first model is Sharia Fintech as a Technology Enabler and Referral Partner, where fintech provides prospective customer referrals to BPRS. The second model is Sharia Fintech as a Technology Enabler and Distribution Channel, functioning as a fund channeling intermediary between BPRS and customers. The third model positions fintech as a technology enabler for creditworthiness assessment, focusing solely on credit scoring activities. The fourth model is Sharia Fintech as a Sharia Peer-to-Peer (P2P) Financing Enabler, in which fintech provides a project marketplace for BPRS to fund, with financing flows conducted through the P2P platform. ANP results show that Model 4 is the most preferred option, while Model 3 is the least recommended. Managerially, BPRS should prioritize Model 4 and establish a joint coordination team with fintech under the supervision of the sharia fintech association.